2013
DOI: 10.1371/journal.pone.0060297
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic Acid Produces Combinatory Anti-Tumor Effects with Cisplatin on Mesothelioma by Increasing p53 Expression Levels

Abstract: We examined anti-tumor effects of zoledronic acid (ZOL), one of the bisphosphonates agents clinically used for preventing loss of bone mass, on human mesothelioma cells bearing the wild-type p53 gene. ZOL-treated cells showed activation of caspase-3/7, -8 and -9, and increased sub-G1 phase fractions. A combinatory use of ZOL and cisplatin (CDDP), one of the first-line anti-cancer agents for mesothelioma, synergistically or additively produced the cytotoxicity on mesothelioma cells. Moreover, the combination ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
9
0
1
Order By: Relevance
“…Cisplatin is known for its ability to bind to and cause cross-linking thereby damage of DNA. It is no wonder that it is able to cause p53 expression and accumulation, as shown in the present study and in many previous studies as well [26,27,28]. Carboplatin is a second generation of cisplatin differing from cisplatin in that it has a bidentate dicarboxylate (CBDCA) ligand in place of the two chloride ligand.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Cisplatin is known for its ability to bind to and cause cross-linking thereby damage of DNA. It is no wonder that it is able to cause p53 expression and accumulation, as shown in the present study and in many previous studies as well [26,27,28]. Carboplatin is a second generation of cisplatin differing from cisplatin in that it has a bidentate dicarboxylate (CBDCA) ligand in place of the two chloride ligand.…”
Section: Discussionsupporting
confidence: 76%
“…Intriguingly, cisplatin is known to bind to and cause cross-linking of DNA to ultimately trigger apoptosis. Both cisplatin and its second generation drug carboplatin have been shown to increase p53 protein level reaching a threshold which leads to the initiation of apoptosis in Hela cells [26,27,28]. In contrast, TP53 gene (encoding p53) status does not correlate with paclitaxel-induced cytotoxicity in various cancer cell lines with differing apoptotic pathways [29].…”
Section: Resultsmentioning
confidence: 99%
“…Recently we demonstrated that the aminobisphosphonate zoledronic acid overcomes the resistance to doxorubicin by reducing the activity of Ras/extracellular signal-regulated kinase1/2 (ERK1/2)/hypoxia inducible factor-1α (HIF-1α)/Pgp axis, and restores a proper recognition by the host immune system in chemo-immunoresistant solid tumors [ 21 ]. Zoledronic acid is known to reduce HMM growth [ 22 ], induce apoptosis [ 23 ], up-regulate p53 [ 24 ], impair the polarization of TAMs towards type 2-phenotype, reduce the synthesis of immunosuppressive cytokines [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is also in vitro evidence that ZA induces apoptosis in mesothelioma cells [ 4 , 6 , 18 ] and favourably affects the host’s immune response to the tumour [ 5 ]. Mouse models of mesothelioma also suggest that ZA inhibits tumour growth and prolongs survival [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is data from a number of cell types to suggest that the aminobisphosphonates may act synergistically with chemotherapy. A recent study evaluating the potential synergistic effect of intrapleural ZA with systemic Cisplatin chemotherapy in a mouse model of mesothelioma showed combination therapy had greater anti-tumour effects than either agent used alone [ 18 ]. We did not evaluate this synergy in the current study, but may be interesting to explore in future trials.…”
Section: Discussionmentioning
confidence: 99%